Tillage Study for Corn and Soybeans: Comparing Vertical, Deep, and No-till - Eric Adee (Kansas Agricultural Experiment Station Research Reports, 2016)
The need for tillage in corn and soybean production in the Kansas River Valley continues to be debated. The soils of the Kansas River Valley are highly variable, with much of the soil sandy to silty loam in texture. These soils tend to be relatively low in organic matter (<2%) and susceptible to wind erosion. Although typically well drained, these soils can develop compaction layers under certain conditions. A tillage study was initiated in the fall of 2011 at the Kansas River Valley Experiment Field near Topeka to compare deep vs. shallow vs. no-till vs. deep tillage in alternate years. Corn and soybean crops will be rotated annually. This is intended to be a long-term study to determine if soil characteristics and yields change in response to a history of each tillage system.
Keywords: tillage; no-till; vertical tillage; corn; soybeans